Mesene Doubleday (Lepidoptera: Riodinidae) from Parque Nacional da Serra do Divisor, Acre, Brazil, with taxonomic notes and the description of a new species - Dolibaina, Diego Rodrigo; Dias, Fernando Maia Silva; Siewert, Ricardo Russo; Mielke, Olaf Hermann Hendrik; Casagrande, Mirna Martins (Zootaxa, 2016)
The species of Mesene Doubleday, 1847 collected at the Parque Nacional da Serra do Divisor, Acre, Brazil (PNSD) are listed and supplemented by taxonomic and behavioral notes. In total, 30 specimens were collected, representing seven species including one new: M. monostigma monostigma (Erichson, [1849]), M. nepticula stigmosa Stichel, 1910, M. eupteryx Bates, 1868 stat. rest., M. paraena Bates, 1868, M. epaphus pyrrha Bates, 1868, M. leucophrys Bates, 1868, and M. gracielae sp. nov. The following notes on the taxonomy of Mesene are proposed: M. eupteryx Bates, 1868 stat. rest. is recognized as a valid species, M. epaphus sertata Stichel, 1910 syn. nov. is a new synonym of M. epaphus pyrrha Bates, 1868, and M. lecointrei P. Jauffret & J. Jauffret, 2008 syn. nov. is a new synonym of M. philonis Hewitson, 1874. Mesene margaretta (White, 1843), M. philonis and M. nola are recognized as closely related. Species encountered at the PNSD are illustrated, including the genitalia of males and females, when available.